Welcoming entanglements with ghosts: Re-turning, re-membering, and facing the incalculable in teacher education. (September 2022) - Furman, Cara E
Posthumanist and antiracist thinkers contend that justice, as articulated by Karen Barad, demands response-ability to ghosts of the past and those yet to come. Normative conceptions of the child do not account for these ghostly engagements. When such normative conceptions direct a teachers' gaze, the child speaking with ghosts may feel they too are not welcome. Without kinship and support grappling with the challenging, even painful, topics that the ghosts raise, they may become discouraged from the larger project of taking response-ability for ghosts in pursuit of justice. In response, the author first repositions the child as rich in potential and a knower who engages with ghosts. Using "travel-hopping" as a methodology, she re-turns to an experience as a teacher who pursued a Master's in Elementary Education as a conversation between her child self, ancestral ghosts, children she worked with, and ghosts those children spoke with. In sharing this experience, the author puts forth travel-hopping through experiences as a valuable method in teacher education. As teachers travel-hop, they can expand their sense of the "child" as capable and powerful in engagements with the more-than-human (broadly defined but focused on ancestral ghosts).